2018
DOI: 10.1186/s12938-018-0451-2
|View full text |Cite
|
Sign up to set email alerts
|

Computer aided sentiment analysis of anorexia nervosa patients’ vocabulary

Abstract: BackgroundDiagnosing and treating anorexia nervosa is an important challenge for modern psychiatry. Taking into account a connection between the mental state of a person and the characteristics of their language, this paper presents developed and tested method for analyzing the written statements of patients with anorexia nervosa and healthy individuals, including the identification of keywords.MethodsDue to the short nature of the texts, which is related to the difficulty of expressing oneself about one’s bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Sentiment analysis of written accounts helps to uncover additional information within a data set ( [36][37]), and our descriptive analysis suggests institutional differences among the mental health narratives (Figs 1-3). These differences were most apparent when examining sentiment scores of students who attended social science programs within elite/Ivy League institutions (Fig 3).…”
Section: Plos Onementioning
confidence: 88%
See 1 more Smart Citation
“…Sentiment analysis of written accounts helps to uncover additional information within a data set ( [36][37]), and our descriptive analysis suggests institutional differences among the mental health narratives (Figs 1-3). These differences were most apparent when examining sentiment scores of students who attended social science programs within elite/Ivy League institutions (Fig 3).…”
Section: Plos Onementioning
confidence: 88%
“…Other work has found differences between men and women when it comes to the emotional content of work-place email [35]. Sentiment analysis has also been used to investigate the mental health status reflected through written language (e.g., [36]), and has been used with geographic information system data to identify communities in need of mental health services in the wake of natural disasters [37].…”
Section: Sentiment Analysismentioning
confidence: 99%
“…It consists of the following steps: 4. The analysis of particular areas of difficulties (from the previous authors' paper [22]).…”
Section: Methodsmentioning
confidence: 99%
“…The previous research showed the relationship between the vocabulary used in the patient's statement and the morbidity. The proposed method intends to provide additional support for the psychologist by developing 6 detailed categories corresponding to the patient's areas of difficulties [22]:…”
Section: The Assessment Of Particular Areas Of Difficultiesmentioning
confidence: 99%
“…3 Several other examples of using NLP for detection and prediction of disease and adverse events are reported in the literature. [34][35][36][37][38]…”
Section: Examplementioning
confidence: 99%